2006
DOI: 10.1021/jo061036y
|View full text |Cite
|
Sign up to set email alerts
|

Radical−Molecule Reactions for Aromatic Growth:  A Case Study for Cyclopentadienyl and Acenaphthylene

Abstract: Polycyclic aromatic hydrocarbon growth from acenaphthylene and cyclopentadienyl was investigated by using the B3LYP/6-31G(d,p) and BH&HLYP/6-31G(d,p) levels of theory as well as transition state theory. The reaction pathways of cyclopentadienyl bearing hydrocarbons are different from those without these moieties and cannot be adequately accounted for by the existing acetylene addition and aryl-aryl addition mechanisms. The reaction mechanisms identified in this paper lead to the formation of fluoranthene, acea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The PAHs with more than two rings may form from two-ring PAH and single-ring compounds. Acenaphthylene is a typical intermediate product that is speculated to be produced via the acetylene addition to naphthalene, and further growth of big PAHs through HACA from acenaphthylene was confirmed by Wang and Violi, who reported that the 1,2 double bond in acenaphthylene has higher reactivity than the 3,4 and 4,5 aromatic bonds, and based on this result, we can easily explain the formation of three- or four-ring PAHs (Figure a). In addition to the HACA mechanism, another pathway based on the reaction of naphthalene and cyclopentadiene is also proposed for the formation of PAHs .…”
Section: Fates Of Carbon Oxygen and Hydrogen In Biomass Pyrolysissupporting
confidence: 60%
“…The PAHs with more than two rings may form from two-ring PAH and single-ring compounds. Acenaphthylene is a typical intermediate product that is speculated to be produced via the acetylene addition to naphthalene, and further growth of big PAHs through HACA from acenaphthylene was confirmed by Wang and Violi, who reported that the 1,2 double bond in acenaphthylene has higher reactivity than the 3,4 and 4,5 aromatic bonds, and based on this result, we can easily explain the formation of three- or four-ring PAHs (Figure a). In addition to the HACA mechanism, another pathway based on the reaction of naphthalene and cyclopentadiene is also proposed for the formation of PAHs .…”
Section: Fates Of Carbon Oxygen and Hydrogen In Biomass Pyrolysissupporting
confidence: 60%
“…Thermochemical parameters, such as enthalpy and Gibbs free energy were calculated using highly accurate composite methods, such as CBS‐QB3 and G3B3 methods. Earlier studies reported that CBS‐QB3 and G3B3 methods will provide better thermochemical results with in chemical accuracy (ie, within 3‐5 kcal/mol) . For all the reactive species, T1 diagnostic values are calculated using CCSD(T)/cc‐pVTZ method.…”
Section: Computational Detailsmentioning
confidence: 99%
“…It was reported that further growth of large PAH via HACA from acenaphthylene was possible (Shulka and Koshi, 2012). Wang and Violi (2006) reported that the 1,2 double bond in acenaphthylene is much more reactive than the 3,4 and 4,5 aromatic bonds, based on which it is easy to explain the formation of fluoranthene, as shown in The formation of a new six-member ring via this mechanism can account for ~25% of the total product yield, whereas the remaining ~75% of the products are CP-PAH molecules formed via a five-member ring closure involving the same ethynyl and ethenyl groups (Kislov et al, 2013). Richter and Howard (2000) and Marsh and Wornat (2000) also reported that it is unlikely to produce phenanthrene from naphthalene via HACA.…”
Section: Mechanism Of Pah Growthmentioning
confidence: 99%